Pengembangan Sistem Layanan Informasi Berbasis Web di SMK Negeri 1 Padang - Yori Saputra; Denny Kurniadi (MASALIQ, 2026)
The use of school websites has been widely discussed in previous studies; however, research that specifically focuses on the development of school information service systems that are collaboratively managed through a multi-user approach remains relatively limited. Common problems include inactive school websites, lack of sustainable management, and content management centralized in a single administrator, which hinder the effectiveness of information services. This study aimed to develop a web-based information service system at SMK Negeri 1 Padang that is capable of integrating school information management in a centralized, structured, and collaborative manner. The study employed a software engineering approach using a Research and Development (R&D) method with a Waterfall development model. Research participants included the administrative office, curriculum staff, teachers, the treasurer, and students, who were selected through purposive sampling. Data were collected through observations, structured and semi-structured interviews, and document analysis, then analyzed using qualitative descriptive and technical analysis. The results showed that the developed system was able to enhance the effectiveness of managing and delivering school information through the implementation of multi-user features, data integration, and the application of the Model–View–Controller architecture in the Laravel framework. These findings contribute to the development of educational information systems by emphasizing the importance of role-based access management in supporting schools’ digital transformation, while also providing a practical solution for improving transparency, accessibility, and the quality of information services for the wider community.